Pola Kemitraan Petani Cabai Merah dengan Koperasi di Desa Andongsari Kecamatan Ambulu Kabupaten Jember - Leilani Nandhita; Muhammad Rondhi (UNEJ e-Proceeding, 2018)
Red chili farmers in Andongsari Village establish partnerships with "Lestari" horticultural cooperatives. Some the reasons of farmers partnering are fluctuating price certainty because market conditions are always changing, the physical nature of red chili is rotten quickly and easily damaged, and uncertain weather.These reasons are problems that can lead to make risks and price risks so farmers decide to partner with cooperatives. Based on this, the purpose of this study was to find out the partnership pattern between red chili farmers in Andongsri Village with " Lestari " horticultural cooperatives.The sample determination method uses purposive sampling. Data collection method uses interview, observation and literature study techniques. The analytical method is descriptive. The results of this study are the partnership pattern formed between red chili farmers and " Lestari " horticultural cooperatives is a pattern of Agribusiness Operational Cooperation (KOA). In the partnership there is a partnership agreement where the “Lestari” horticultural cooperative has the rights and obligations to get the production according to the agreement, cancel the contract, lend the product, guarantee the market and prices, and provide technical guidance. Farmers have the right and obligation to obtain credit for inputs, get paid as promised, sell red pepper to cooperatives, and pay loans. However, the partnership has problems such as quantity and quality that are not in accordance with the agreement, and cooperatives that do not pay the results on time.